Impact of Optimal Timing of Intake of Multi-Ingredient Performance Supplements on Sports Performance, Muscular Damage, and Hormonal Behavior across a Ten-Week Training Camp in Elite Cyclists: A Randomized Clinical Trial - Diego Fernández-Lázaro (MDPI AG, 2021)
Multi-ingredient performance supplements (MIPS), ingested pre- or post-workout, have been shown to increase physiological level effects and integrated metabolic response on exercise. The purpose of this study was to determine the efficacy of pre-and post-training supplementation with its own MIPS, associated with CHO (1 g·kg−1) plus protein (0.3 g·kg−1) on exercise-related benchmarks across a training camp for elite cyclists. Thirty elite male cyclists participated in a randomized non-placebo-controlled trial for ten weeks assigned to one of three groups (n = 10 each): a control group treated with CHO plus protein after training (CG); a group treated with MIPS before training and a CHO plus protein after training, (PRE-MIPS); a group treated with CHO plus protein plus MIPS after training, (POST-MIPS). Performance parameters included (VO2max, peak; median and minimum power (W) and fatigue index (%)); hormonal response (Cortisol; Testosterone; and Testosterone/Cortisol ratio); and muscle biomarkers (Creatine kinase (CK), Lactate dehydrogenase (LDH), and Myoglobin (Mb)) were assessed. MIPS administered before or after training (p ≤ 0.05) was significantly influential in attenuating CK, LDH, and MB; stimulating T response and modulating C; and improved on all markers of exercise performance. These responses were greater when MIPS was administered post-workout.